Safe passages : (Island Press, 2010)
Safe Passages brings together in a single volume the latest information on the emerging science of road ecology as it relates to mitigating interactions between roads and wildlife. This practical handbook of tools and examples is designed to assist individuals and organizations thinking about or working toward reducing road-wildlife impacts